2016
DOI: 10.1016/j.eats.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Opening-Wedge Proximal Tibial Osteotomy

Abstract: Varus knee malalignment caused by medial compartment arthritis results in progressive asymmetric wear of the tibiofemoral joint. This wear can cause progressively painful gonarthrosis. Surgical methods to address varus knee malalignment include lateral closing-wedge proximal tibial osteotomy, medial opening-wedge osteotomy, and arthroplasty. Medial opening-wedge proximal tibial osteotomy is an effective procedure for restoring proper coronal alignment and reducing knee pain. In this technical note, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…OWHTO is an accepted and reliable procedure for the treatment of medial compartmental osteoarthritis in young, active individuals with varus deformity [ 8 , 9 , 11 13 , 30 ]. However, during OWHTO surgery, extensive soft tissue destruction and osteotomy gap creating induce intraoperative and postoperative bleeding, which prolong recovery time and enhance the risk of infection [ 12 14 ]. In our previous study, we confirmed that the blood loss was 383.3 ± 181.3 ml in patients undergoing OWHTO [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OWHTO is an accepted and reliable procedure for the treatment of medial compartmental osteoarthritis in young, active individuals with varus deformity [ 8 , 9 , 11 13 , 30 ]. However, during OWHTO surgery, extensive soft tissue destruction and osteotomy gap creating induce intraoperative and postoperative bleeding, which prolong recovery time and enhance the risk of infection [ 12 14 ]. In our previous study, we confirmed that the blood loss was 383.3 ± 181.3 ml in patients undergoing OWHTO [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Open-wedge high tibial osteotomy (OWHTO) is a reliable option for knee osteoarthritis with varus malalignment in young, active people [ 8 11 ]. This technique is easy to learn and allows precise correction during the surgical procedure; however, it creates an osteotomy gap and increases the risk of bleeding theoretically [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using the fixed-effects model, no significant difference was found in the drainage amount on POD2 between the TXA and NTXA groups (WMD = 4.17, 95% CI [À7. 48,15.83], P = 0.48) (Fig. 7B, Fig.…”
Section: Drainage Amount On Pod2mentioning
confidence: 94%
“…[11][12][13][14] However, perioperative blood loss is theoretically high during HTO, with bone bleeding from the osteotomy gap. 15 This can increase the incidence of wound complications, anemia, transfusions, and bone non-union, affecting patients both physically and mentally. Some studies have reported total blood loss of more than 800 mL, 16,17 delayed wound healing of 1.9%, and superficial wound infection of 1%.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, opening-wedge HTO has attracted much interest due to its advantages over closing-wedge HTO, in-cluding not violating the proximal tibiofibular joint, no alteration in the length of fibular collateral ligament and providing the opportunity for a precise intraoperative correction. However, it is also reported to increase the posterior tibial slope (PTS) more than closing-wedge HTO (7). Thus, several investigations have aimed at evaluating the change of PTS following opening-and closing-wedge HTO.…”
mentioning
confidence: 99%